Bronchiolitis Management: Development of an Australasian Evidence Base - O'Brien, Sharon Lea (Curtin University, 2022)
Bronchiolitis is a common respiratory illness and the leading cause of hospitalisation for infants in Australia and New Zealand. Management for bronchiolitis is well defined and constitutes supportive treatment. However, despite the availability of high-level evidence, there remains substantial variation in the care. This research provides clinicians with information and resources to promote the delivery of evidenced-based care to infants presenting or admitted to hospital with bronchiolitis.